Upaya Konvergensi Kebijakan Pencegahan Stunting di Kota Padang - Muhammad Iqbal; Rahmadani Yusran (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2021)
This research was conducted using a qualitative approach. This study aims to analyze efforts to implement convergence of stunting prevention policies in the city of Padang. The data collection methods used were interviews and documentation. The data source was obtained through data and information on all OPDs in Padang City. The results of this study indicate that efforts to implement convergence of stunting prevention policies in the city of Padang have not been implemented according to the convergence stage. This is because first, efforts at the planning stage have not been implemented optimally because there is no Regional Government Work Plan (RKPD) that has been made regarding stunting. Second, efforts at the implementation stage have not been carried out optimally because there is no task force in implementing stunting prevention actions. Third, efforts at the evaluation stage have not been implemented optimally because the evaluation has not been centralized and implemented based on the work program of each Regional Apparatus Organization (OPD).